(untitled) (Damascus University Journal of agriculture sciences, 2021)
The study was conducted to survey and identify species of wood borer (Cerambyx spp) in southern and middle regions of Syria in 15 places Damascus, Countryside of Damascus, Alqunetera, Homs, Hama, Daraa and Alswida during 2012 & 2016, Samples of adults were collected during the period from April to September. All specimens were identified by using international keys of cerambycidae by using scanning electron microscope (SEM). Adults were classified in 4 species C.dux,C.nodulosus, C.miles, C.carinatus. The specie C.dux was with highest distribution percentage (52,31%),while The specie C.miles got lowest distribution percentage (10,41%).